Penerapan Metode CART pada Pengklasifikasian Bekerja dan Pengangguran di Kabupaten Subang - Ilma Nabila; I Made Sumertajaya; Mulianto Raharjo (Department of Statistics, IPB, 2022)
Unemployment is a complex problem faced by developing countries, including Indonesia. The high unemployment rate in Indonesia impacts poverty, so that the government seeks to carry out economic development. Subang is one of the districts that contributed 8,68 percent of the open unemployment rate in 2019 and increased by 9,48 percent in 2020. The incessant growth of industrial estates and smart city program development in Subang is one of the efforts to reduce unemployment. This study used a classification and regression tree (CART) to determine the factors that influenced unemployment status in Subang Regency. The advantage of the CART method is easy to interpret the results of the analysis. However, the accuracy of the classification tree is relatively low due to data imbalance. Therefore, this study used SMOTE method to deal with this problem. The optimal classification tree was formed from 17 terminal nodes and 6 explanatory variables. 7 terminal nodes represent work as work, and 10 terminal nodes represent unemployment as unemployment. The 6 explanatory variables consist of marital status (X3), attending job training (X5), the position in the family (X4), the education level (X2), gender (X1), and age (X6).